Health Risk Assessment for the Exposure of Workers to BTEX at the Gasoline Stations - Nguyen Thanh Giao; Phan Kim Anh; Huynh Thi Hong Nhien (Journal of Applied Sciences and Environmental Management, 2021)
The study was conducted to assess the health risks of workers due to exposure to toxic gases including benzene, toluene, ethylbenzene, m, p-xylene, o-xylene, formaldehyde and acetaldehyde at gasoline retail stations. In this study, data on the  concentrations of the toxic gases were collected from the previously published studies in the qualified scientific journals. The health risk assessment was followed by the process of the United States Environment Protection Agency (U.S. EPA). The results show that the concentrations of benzene, toluene, ethylbenzene, m, p-xylene, o-xylene, formaldehyde, and acetaldehyde were in the range of 12.40 - 357.5, 12.47 - 574.17, 2.05 - 156.5, 4.57 - 218, 2.36 - 77.04, 3.64 - 153.93 and 1.27- 27.83 µg/m3 , respectively. Life time cancer risk for gasoline station workers due to exposure to benzene, ethylbenzene, formaldehyde, and acetaldehyde was calculated in the ranges of 2.13x10-5 - 6.14x10-4 , 4.96x10-7 - 3.79x10-5 , 4.81x10-6 - 2.03x10-4 , and 7.99x10-7 - 1.75x10-5 , respectively. For non-carcinogenic  compounds, the hazard index due to benzene, toluene, m, p-xylene, o-xylene were respectively in the range of 0.13 - 3.81, 7.97x10-4 -  0.04, 0.01 - 0.70 and 0.01 - 0.25. The findings revealed that there is high risk of cancer and non-cancer for the workers working at the gasolines stations if they are not taking good preventive measures. The calculation showed that the limit levels of benzene, toluene, ethylbenzene, xylene, formaldehyde and acetaldehyde should be reduced to 5.82x10-4 , 15.64, 4.13x10- 3 , 0.31, 7.57x10-4 and 1.59x10-3 mg/m3 , respectively to meet the safety levels for the workers at the gasoline stations.